FACTORS CONTRIBUTING TO INCREASED CASES OF EARLY WEANING AMONG MOTHERS OF CHILDREN BELOW 6 MONTHS AT KAYUNGA REGIONAL REFERRAL HOSPITAL, KAYUNGA DISTRICT. A CROSS-SECTIONAL STUDY. - Katumba, Noah; Nabukenya , Sharifah (Student’s Journal of Health Research Africa, 2024)
Introduction; The specific objectives were to assess the individual, Health facility, and community-based factors contributing to increased cases of early weaning among mothers of children below 6 months of age in Kayunga National Referral Hospital Methodology The study was designed with a simple random sampling of the sample population. Data were collected from a sample size of 50 respondents using semi-structured questionnaires written in the English language with open-ended and closed-ended questions and the tools include sheets and pens entered in the computer program presented in tables and figures. Results Regarding Individual factors 86% were employed, 68% started using bottle feeding before 6 months, 64% used supplementary feeding for children below 6 months, and 54% returned to work within 6 months. In regards to health facility-related factors, 56% took their children to nursing centers, 66% were educated on when and how to breastfeed, and 68% were educated on maternal nutrition during lactation. Regarding community-based factors, 76% of the mothers in their communities supported exclusive breastfeeding for 6 months, 62% of their children didn’t receive any herbal medication, and 84% were from monogamous families. Conclusion Despite the low individual, health facility, and community factors, contributing to increased cases of early weaning among mothers of children below 6 months of age at Kayunga Regional Referral Hospital, the researcher still recognizes that there is a need for mothers to carry out exclusive breastfeeding for the first 6 months of age for proper growth and development of the children. Recommendations The Ministry of Health should enforce the health team so that they can fully provide health services in terms of providing Nutritional Education to mothers on foods to eat during the lactation period and also on how and when to breastfeed.